Potencial de solubilização de fosfato e identificação molecular de bactérias isoladas de solos sob cultivo de cana-de-açúcar - Castro, Rosa Betânia Rodrigues de [UNESP] (2015)
The stillage is a by-product of the production of ethanol and sugar. There is a huge concern for professionals in the environmental area in relation to its final destination, the high degree impactful when discarded into the environment. The plants the sugarcane industry lately have been using the fertilization with vinasse in crops thanks to large concentrations of nutrients present in this effluent. Study on the composition of the microbiota and physiology of soils subjected to irrigation vinasse can be of great importance in finding products of biotechnological interest since this residue enhances the microbial activity in environments where it is applied. The purpose of that study was the molecular characterization, by sequencing the 16S rRNA gene in order to identify the phylogeny of four bacterial isolates obtained from sugarcane cropland with vinasse management, and assess the capacity of phosphate solubilization of these isolated amid NBRIP and relate the data with best practices in agriculture. Isolated LGA01-EV05 showed high sequence similarity to Curtobacterium albidum, isolated LGA02-EV08 denotes similarity to Brevibacillus nitrificans, the LGA03-V20B isolated and LGA04-V20G show high degree of similarity between themselves and with Sinomonas soli. Taxa of isolates are belonging to the phyla Firmicutes and Actinobacteria. As to the evaluation of the bacterial potential for phosphate solubilization, the four isolates were efficient in solubilizing phosphate amid NBRIP. However, it was observed that there was no statistical difference between the LGA02-EV08 and LGA04-V20G groups, with the best phosphate solubilizing bacteria. They had an income about four times the LGA03-V20B group, the worst among the analyzed